Awareness about basic life support among undergraduate medical students before and after clinical exposure in a tertiary care hospital attached to a medical school in South India (Asian Journal of Medical Sciences, 2024)
Background: Knowledge of basic life support (BLS) is one of the life-saving measures that every medical undergraduate student must possess.Aims and Objectives: This study focused on knowing the level of knowledge in fresh medical undergraduate entrants (knowledge A [KA]) and 3rdyear students with clinical exposure but no BLS training (knowledge B [KB]). We also assessed the knowledge in 1st-year students (retention A [RA]) soon after foundation course and compared it with retained knowledge after 6 months (retention B [RB]).Materials and Methods: This non-randomized multigroup cross-sectional study was done on medical undergraduate students in a tertiary care hospital attached to a medical school in South India. A validated questionnaire with 25 questions assessing knowledge of BLS was formulated and administered to 508 medical students.Results: After analyzing data in SPSS V24, the mean scores in KA and KB were 11.03±4.33 and 13.95±5.43, respectively, with a P50%, clinical exposure had some effect on mean scores in medical undergraduates. Mean scores in RA and RB were 23.16±5.09 and 16.17±6.97, respectively, with P